ANALYSIS OF TRAFFIC BEHAVIOR IN MILLENIAL GENERATION - SUHARMANTO SUHARMANTO; Shinta Mayasari (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2020)
According to the Republic of Indonesia National Police data for 2017, an average of 3 people dies every hour due to road accidents, caused by a human, vehicle, infrastructure, and environmental factors. The objective describes traffic behavior in millennial generation. The research method used is a mixed method. The location of the study was conducted in the city of Bandar Lampung and Pesawaran district. This study used a questionnaire and an interview sheet. The Mann Whitney test was used to determine differences between groups. Qualitative data is formulated for the conclusion. The findings of the research data shown there is no difference in driving knowledge scores between program and non-program schools, and there is no difference in knowledge scores about traffic signs between a program and non-program schools. Based on the results of interviews in 4 schools that did not receive the Police Goes to School Education program, 2 of them in the past 3 years did not receive the program, while 2 others have never received the Police Goes to School education program. Menurut data Kepolisian Negara Republik Indonesia tahun 2017, rata-rata 3 orang meninggal setiap jamnya akibat kecelakaan di jalan raya yang disebabkan oleh faktor manusia, kendaraan, infrastruktur, dan lingkungan. Tujuan penelitian mendeskripsikan perilaku lalu lintas pada generasi milenial. Metode penelitian yang digunakan adalah metode campuran. Lokasi penelitian dilakukan di Kota Bandar Lampung dan Kabupaten Pesawaran. Penelitian ini menggunakan kuesioner dan lembar wawancara. Tes Mann Whitney digunakan untuk menentukan perbedaan antar kelompok. Data kualitatif dirumuskan sebagai kesimpulan. Temuan data penelitian menunjukkan tidak ada perbedaan skor pengetahuan mengemudi antara sekolah dengan program dan non-program, dan tidak ada perbedaan skor pengetahuan tentang rambu lalu lintas antara sekolah dengan program dan non-program. Berdasarkan hasil wawancara di 4 sekolah yang tidak menerima edukasi dalam program Police Goes to School, 2 di antaranya dalam 3 tahun terakhir tidak menerima program tersebut, sedangkan 2 lainnya tidak pernah menerima program pendidikan Police Goes to School.